Therapies for obsessive-compulsive disorder: Current state of the art and perspectives for approaching treatment-resistant patients - Swierkosz-Lenart, Kevin; Dos Santos, Joao Flores Alves; Elowe, Julien; Clair, Anne-Hélène; Bally, Julien F.; Riquier, Françoise; Bloch, Jocelyne; Draganski, Bogdan; Clerc, Marie-Thérèse; Pozuelo Moyano, Beatriz; von Gunten, Armin; Mallet, Luc (Frontiers in Psychiatry, 2023)
Even though obsessive compulsive disorder (OCD) is one of the ten most disabling diseases according to the WHO, only 30-40% of patients suffering from OCD seek specialized treatment. The currently available psychotherapeutic and pharmacological approaches, when properly applied, prove ineffective in about 10% of cases. The use of neuromodulation techniques, especially Deep Brain Stimulation, is highly promising for these clinical pictures and knowledge in this domain is constantly evolving. The aim of this paper is to provide a summary of the current knowledge about OCD treatment, while also discussing the more recent proposals for defining resistance.